(untitled) ([1st American ed.], 1963)
Geisha in Rivalry, first published in 1918, is set against the backdrop of Tokyo's Shimbashi geisha district. The story of three geisha, imperious Rikiji, gaudy Kikuchiyo, and the naïve heroine Komayo, Geisha in Rivalry follows them in their search for a place in a world that offers no easy route of escape from their profession. With a full cast of vivid characters playing out their dramas of illicit love, shady intrigue and unrelenting rivalry, Geisha in Rivalry is the sordid but fascinating tale of Komayo, her lovers, and the women who conspire to steal them from her.
Keywords: Japanese literature,Japan fiction